Effects of sika deer antler protein on immune regulation and intestinal microbiota in mice - Kaiyue Liu; Ke Zhang; Yang Yang; Ying Zong; Zhongmei He; Weijia Chen; Jianming Li; Rui Du (Journal of Functional Foods)
The medicinal use of pilose antler was first described in Shennong's Classic of Materia Medica for treating kidney yang deficiency. Therefore, in this study, sika deer antler protein (SDAP) was used as a component analysis and its impacts on the immunomodulatory effects of RAW264.7 cells and kidney yang deficiency mice, as well as the intestinal flora of mice, were investigated. The results showed that SDAP could regulate the secretion of associated factors and the expression of genes and proteins of NF-κB-related signaling pathway in RAW264.7 cells induced by lipopolysaccharide and kidney yang deficiency mice. Additionally, SDAP could regulate intestinal homeostasis by increasing the abundance of beneficial bacteria Lactobacillus and Clostridium, reducing the abundance of pathogenic bacteria Proteobacteria, and maintaining some bacterial homeostasis in kidney-yang deficiency mice, so as to decrease intestinal edema, effectively improve intestinal microecology, and improve the immune function of the organism.